Evaluation of service accuracy in novice tennis athletes at PELTI pangkep: Quantitative study of the hewitt test - Aprilo, Ians; Arfanda, Poppy Elisano; Mappaompo, M Adam; Yasriuddin, Yasriuddin; Awaluddin, Awaluddin; Yusnadi, Yusnadi; Priambodo, Anung (Universitas Tanjungpura, 2025)
Background. Accuracy in serving contributes to an athlete's game consistency, making them more unpredictable for opponents. This not only affects the technical aspect but also the psychological one, as players with accurate serves are able to maintain mental pressure on the opponent, which can ultimately change the dynamics of the match. Objectives. This research evaluates service accuracy in beginner tennis athletes at PELTI Pangkep, an aspect often overlooked in sports literature. The research gap lies in the lack of studies concerning service accuracy, especially among beginner athletes. The research aims to measure tennis service accuracy. Methods. This research is a quantitative descriptive study with a survey design conducted on January 23, 2024, involving 20 beginner tennis athletes aged 10